Method and composition for making watertight cement based concrete product utilizing silica nanoparticles and rice husk ash - Abdul Rashid, Suraya; Naji Givi, Alireza; Abd. Aziz, Farah Nora Aznieta; Mohd Salleh, Mohamad Amran (2012)
A method of production of a watertight ternary blended concrete product to highly reduce multiple water absorption values includes the steps of providing a cement mortar mixture, introducing ultrahigh reactive activators to the cement mortar mixture to lower porosity by densifying the cement mortar mixture and accelerating multiple cement hydration particles. Particularly, the activators include multiple nanoparticles. The method further includes, mixing the cement mortar mixture and the multiple nanoparticles with an inorganic binder and water to form the concrete product.